Nursing diagnoses in women deprived of freedom - Izabelle de Freitas Ferreira; Tatiane Gomes Guedes; Sheila Coelho Ramalho Vasconcelos Morais; José Cristovam Martins Vieira; Marcelle Guimarães de Mello; Francisca Márcia Pereira Linhares (Rev Rene)
Objective: to analyze the nursing diagnoses profile of women deprived of freedom, using the International Classification for Nursing® Practice version 1.0. Methods: a descriptive study, conducted with 186 women deprived of freedom. Nursing Diagnoses were extrapolated based on the clinical data of the participants, collected through a structured form and clinical reasoning. Results: there were 44 nursing diagnostic statements, among the most common, there were: infection risk (70.9%); fluid intake, decreased (61.2%); Sleep, impaired (60.7%); tobacco abuse, started (51.6%); health seeking behavior, committed (50.0%). Conclusion:the diagnoses are related to factors that compromise the biopsychosocial health. The nurse, health staff member in the prison setting, must recognize and assess the individual and collective needs of women deprived of freedom. The inference of nursing diagnoses, based on clinical reasoning, contributes to a humanized, empathic and special care.